Mapping spatial cultures: contributions of space syntax to research in the urban history of the nineteenth-century city. (17th August 2020) - Griffiths, Sam; Vaughan, Laura
Abstract: The theory and methods of space syntax can help to rebalance the prevailing cultural perspective, which views maps as ideological representations, with an analytical approach that emphasizes maps as sources for understanding space and spatial relationships embedded in built forms. The quantitative descriptions of urban street networks produced by space syntax analyses can be used to formulate and test hypotheses about patterns of urban movement, encounter and socio-economic activity in the past that can help in the interpretation of other historical source materials to give an overall account of urban spatial culture. In this article, the authors explain how space syntax, a theory and method originally developed in the field of architectural research, is making a distinctive contribution to research in social and urban history. The key principles of the method are explained by clarifying the relationship of space syntax to HGIS (Historical Geographical Information Systems) and through a worked example of research undertaken into political meeting places. A survey of research into the urban history of the nineteenth-century city using space syntax is used to highlight a number of important methodological themes and also demonstrates the range of innovative contributions that this interdisciplinary approach is able to advance. A final, theoretical, section reflects on maps and the practice of 'mapping' from a space syntax perspective.